Diversity of Heamatogenetic Markers in Kirkuk Population - AI-Taei, S. M.; Nader, M. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Immuno-haematological genetic markers study was carried out to understand the genetic background variations among Kirkuk (Iraq) indigenous population. A cross-sectional study of 179 patients with thalassemia major was conducted in Kirkuk. A detailed review was undertaken to define the relationships between ethnic origins, phenotype and immuno-genetic markers uniformity in relation to genetic isolation and interethnic admixture. A total of 179 thalassemia major patients were subjected to analysis in the hereditary blood diseases centre, including (18(10.05 %)) of intermarriages between different ethnic groups origin, whereas the overall consanguinity marriage rate was estimated at (161 (89.9%)) including (63(35.1%)) for first cousin marriages origin. Out of the 161 cases, 63(39.1%), 52(32.2%) and 46(28.5%) represent Kurdish, Arab and Turkmen ethnic groups, respectively. The distribution of thalassemia major cases within ethnic groups relatively differs (d.f.2, P< 0.2). Arab, (46 (28.5%)) represents the lowest disease (thalassemia) sufferer group because of its relative high rate of outbreeding (14, 77.7%).Blood groups (ABO) and Rhesus (D) genetic marker show no significant differences among the triethnic sample groups (thalassemia patients) of Kirkuk with a preponderance of blood group O. No apparent relationship was found between ABO or Rhesus blood groups and the frequencies of thalassemia major cases. The study showed a relative genetic heterogeneity and diversity with respect to the immuno-hematological genetic markers. Further, all ethnic populations from Kirkuk were found to harbor thalassemia major genetic marker.